The Influence of Expenditure Capital Level, Regional Dependence Level and Independence Level on Growth of The Regional Human Development Index - Fithtiah Napu; Arifin; Yenni; Melina; Ciptawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The goal of this study is to determine the relationship between the human development index and the quantity of regional capital investment, the degree of regional dependence, and the degree of regional financial independence. The Human Development Index (HDI) is the dependent variable, whereas the degree of regional financial independence, the degree of regional financial interdependence, and the degree of capital spending are independent factors. The panel data analysis in this study makes use of the fixed effect model (FEM) methodology. The results show that the degree of regional financial dependence, degree of regional financial independence, and degree of capital investment all considerably and favorably influence the Human Development Index (HDI). It partially depicts how the degrees of regional financial dependence, financial independence, and capital spending have a significant and beneficial impact on the Human Development Index (HDI).